Metallic to variable-range-hopping transition controlled by oxygen content in La-Sr-Cu-O - Osquiguil, E.J.; Civale, L.; Decca, R.; De La Cruz, F. (American Physical Society, 1988)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina